2019
DOI: 10.1371/journal.pone.0217211
|View full text |Cite
|
Sign up to set email alerts
|

Proof of principle: Physiological transfer of small numbers of bacteria from mother to fetus in late-gestation pregnant sheep

Abstract: The fetus is thought to develop in a sterile environment in utero. Long standing dogma that “the uterus and the feto‐placental unit is “sterile” is based primarily on microbiological culture‐based techniques that were unsuccessful in growing “culture resistant” bacteria or intracellular bacteria. We have reported the presence of low numbers of bacteria in tissues from normal sheep fetuses in pregnancies not complicated by infection. The exposure of the fetus to bacteria might aid neonatal survival by informing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 28 publications
(44 reference statements)
4
25
0
Order By: Relevance
“…Prior to its birth, it is presumed that the unborn is free of microbial flora, and that at birth, the infant first comes in contact with the resident microbial flora of the mothers’ vagina if birth was through the natural birth canal, or the microbial flora of the mothers’ skin if birth was through cesarean section [ 20 , 21 , 22 ]. Although some studies [ 23 , 24 , 25 ] have suggested the early inoculation of the fetus with bacteria and bacteria DNA through the placenta. The study by de Goffau et al [ 26 ] reported that the human placenta has no microbiome.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to its birth, it is presumed that the unborn is free of microbial flora, and that at birth, the infant first comes in contact with the resident microbial flora of the mothers’ vagina if birth was through the natural birth canal, or the microbial flora of the mothers’ skin if birth was through cesarean section [ 20 , 21 , 22 ]. Although some studies [ 23 , 24 , 25 ] have suggested the early inoculation of the fetus with bacteria and bacteria DNA through the placenta. The study by de Goffau et al [ 26 ] reported that the human placenta has no microbiome.…”
Section: Resultsmentioning
confidence: 99%
“…The lungs have previously been considered a sterile environment, and assessment of pulmonary disease has been examined from a bacterial pathology perspective (41). recently, 16s ribosomal rna studies and metagenomics revealed the presence of a flexible microbiota in the upper and lower respiratory tract, blood, placenta and amniotic fluid (42). increasing evidence has shown that bacteria are present in the lungs and serve key roles in fatal pneumonia, which can be both beneficial and harmful (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen pregnant ewes of known gestational age were sampled for this study; all ewes and their fetuses/lambs had undergone surgery to place fetal catheters and/or telemetry devices for study in other protocols (Table 4). Ewes were housed and euthanized, and tissues were sampled as described by Yu et al (12). For all animals, the tissues were collected from the fetus/lamb, including liver, lung, spleen, and stool.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently reported evidence that bacterial cell components can be found in the late-gestation fetus after inoculation of the mother with live bacteria. In that study, intravenous inoculation of pregnant ewes with 100 CFU of green fluorescent protein (GFP)-expressing Staphylococcus aureus resulted in the detection of GFP plasmid DNA and GFP protein in placenta and fetal tissues 4 to 6 days later (12). The inoculation did not cause any clinical signs of infection or septicemia in the ewes (which maintained normal body temperature and food intake).…”
Section: Dry Necropsy Tablementioning
confidence: 99%